2003
DOI: 10.1190/1.1623645
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive AVO classification

Abstract: In this paper a new classification for AVO responses is proposed. This classification covers all possible AVO responses and is independent of the fluid content of the beds. In 1989 Rutherford and Williams introduced a threefold classification of AVO (amplitude versus offset) characteristics for seismic reflections from the interface between shales and underlying gas sands. The classification scheme they proposed has become the industry standard and has proven its validity and usefulness in countless exploratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…6c shows amplitude variations of both cases of Figs 6a and 6b on a graph with the relative amplitude versus the angle. As many authors reported, the former is a well-known pattern of waterbearing rocks while the latter is one of the typical patterns of gas-bearing rocks e.g., 20,21) .…”
Section: Avo Analysismentioning
confidence: 85%
“…6c shows amplitude variations of both cases of Figs 6a and 6b on a graph with the relative amplitude versus the angle. As many authors reported, the former is a well-known pattern of waterbearing rocks while the latter is one of the typical patterns of gas-bearing rocks e.g., 20,21) .…”
Section: Avo Analysismentioning
confidence: 85%
“…The classifications expand and redefine the commonly used AVO type from Rutherford-Williams and Castagna-Swan. The difference between Young-Piccollo and Rutherford-Williams scheme is in the sand layer, which is designated to be conforming or nonconforming [10]. The conforming sands are re-divided to consider AVO response type 5.…”
Section: Methodsmentioning
confidence: 99%
“…The conforming sands are re-divided to consider AVO response type 5. The AVO response type is determined based qudrant classification that consider the AVO attributes (intercept and gradient) [10].…”
Section: Methodsmentioning
confidence: 99%
“…A classification of AVO effects. Ten types of AVO effects are conceptually shown for gas‐bearing and nongas‐bearing rocks [ Young and LoPiccolo , 2003]. …”
Section: Avo Analysismentioning
confidence: 99%
“…On the other hand, in Figures 8b and 8d, the amplitudes are negative at small angles and change to positive values at large angles. The former is categorized in type −1 and the latter is type −5 according to the classification of nongas‐bearing sands by Young and LoPiccolo [2003].…”
Section: Avo Analysismentioning
confidence: 99%